2020
DOI: 10.1002/jsfa.10722
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant quantification in different portions obtained during olive oil extraction process in an olive oil press mill

Abstract: BACKGROUNDDifferent antioxidant compounds are generally transferred from olives to olive oil during the production process. This work characterized the principal total bioactive compounds (tocopherols and phenols) in olives, olive oil and by‐products of four cultivars grown in Calabrian areas (southern Italy), considering the effect of harvesting period. Antioxidant capacity, total and individual phenolic compounds were also analysed.RESULTSDrupes, olive paste, pomace and olive wastewater showed similar phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…Our results also confirmed positive correlation between the DPPH and ABTS methods (r = 0:902). Furthermore, the ABTS assay resulted in a much higher value of antioxidant capacity, which was also confirmed in other studies [30,31]. De Bruno et al [31] reported that it could be due to the different composition of analyzed samples containing hydrophilic and lipophilic antioxidant compounds.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Our results also confirmed positive correlation between the DPPH and ABTS methods (r = 0:902). Furthermore, the ABTS assay resulted in a much higher value of antioxidant capacity, which was also confirmed in other studies [30,31]. De Bruno et al [31] reported that it could be due to the different composition of analyzed samples containing hydrophilic and lipophilic antioxidant compounds.…”
Section: Resultssupporting
confidence: 73%
“…Furthermore, the ABTS assay resulted in a much higher value of antioxidant capacity, which was also confirmed in other studies [30,31]. De Bruno et al [31] reported that it could be due to the different composition of analyzed samples containing hydrophilic and lipophilic antioxidant compounds. The ABTS assay is more applicable to both hydrophilic and lipophilic antioxidant systems, whereas DPPH assay is more related to hydrophobic system response [32].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…During oil extraction, many of these secondary metabolites can be destroyed or degraded or transferred in olive oil mill waste. At the end of the extraction process, olive oil contains 1–2% of the total phenol content (TPC) of drupes, so the residual antioxidant compounds would be lost in olive mill wastewater and pomace [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, recent reports propose new methods based on nanocentrifugation and ultrafiltration to revalorize the olive wastewater [ 6 , 7 ]. Chemical characterization studies revealed that some bioactive compounds are transferred from olives to oil and their by-products and waste during the oil production process [ 8 ]. Specifically, OP, OWW, and OLs contain bioactive compounds including secoiridoids, squalene, flavonoids, lignans, phytosterols, tocopherols, and phenols.…”
Section: Introductionmentioning
confidence: 99%